Work Productivity of Employees at The Regional Financial and Assets Management Agency of Konawe District - Nartin Nartin; Yuliana Musin (LAFADZ JAYA Publisher, 2022)
The role of professionalism of employes is determined by the level of abilty of employes who are reflected through everyday behavior in the organizations. the ability of employes in providing public services leads to the achievement of organizational goals that have been planned previously. The regional financial and asset management agency of konawe regency. The results showed that the work productivity of the employees of the Konawe district financial and asset management agency can be achieved in terms of aspects, (a) ability, (b) improving the results achieved, (c) the spirit of work, (d) self deflopment, and (e) quality. factors that influence the work productivity of employes of the konawe district financial and asset management agency, which consist of factors. Motivation, with the motivation of employees to work more productively, Discipline, namely employees who work by obeying the rules and regulations existing rules, Work, ethics employees at work have character, attitude and ethics. Skills, namely employees in work are supported by work skills acquired through education and training or technical guidance. education, namely employees thou who have formal education affect the work ability of employees.